Open Source Systems: Towards Robust Practices 13th IFIP WG 2.13 International Conference, OSS 2017, Buenos Aires, Argentina, May 22-23, 2017, Proceedings - Balaguer, Federico; Di Cosmo, Roberto; Garrido, Alejandra; Kon, Fabio; Robles, Gregorio; Zacchiroli, Stefano (IFIP Advances in Information and Communication Technology,, 2017)
This book is open access under a CC BY license. This book constitutes the refereed proceedings of the 13th IFIP WG 2.13 International Conference on Open Source Systems, OSS 2017, held in Buenos Aires, Argentina, in May 2017. The 16 revised full papers and 3 short papers presented were carefully reviewed and selected from 32 submissions. The papers cover a wide range of topics related to free, libre, and open source software (FLOSS), including: licensing, strategies, and practices; case studies; projects, communication, and participation; tools; and project management, development and evaluation.